The pricing of firms with expected losses/profits: The role of January. (27th November 2017) - Chiu, Peng‐Chia; Nekrasov, Alexander; Shevlin, Terry
Abstract: We examine the role of January in the relation between expected losses/profits and future stock returns. We predict and find that the relation between expected losses/profits and future returns reverses from the usual positive relation in non‐January months to a negative one in January. The reverse January relation is consistent across sample years, is observed in the United States and international markets, and is incremental to other variables associated with January returns. At least part of the reverse January relation is explained by tax‐loss selling. Further analysis shows that the reverse January relation results in a temporary price drift away from fundamental value . In other words, we find that abnormal positive (negative) future returns do not always indicate past under(over)valuation. Overall, our results illustrate the importance of controlling for the effect of January when examining how investors price expected losses/profits.